The electronic commerce development in retail of high-tech consumer goods - A. V. Veretyokhin (Вестник университета, 2019)
The features and prospects of e-commerce in the retail of high-tech consumer goods in Russia and in the world have been considered. The main threats and challenges to the development of the industry and its advantages in the context of digitalization have been identified. The influence of the digital technologies progress, competition strengthens, legal environment, market capacity, advanced technologies application, customer behavior on the Internet High-Tech trading development has been established. The need for Russian market operators to introduce innovative methods ofproduct promotion and sales methods, that are common among the world’s leading Internet sales has been defined. The main directions of development to increase customer loyalty are integration of retailers with social networks, personalization and omnipresence, - have been highlighted.